Interventions to Prevent Spontaneous Preterm Birth in Women With Singleton Pregnancy Who Are at High Risk: Systematic Review and Network Meta-Analysis. Issue 4 (21st December 2022) - Care, A.; Nevitt, S.J.; Medley, N.; Donegan, S.; Goodfellow, L.; Hampson, L.; Tudur Smith, C.; Alfirevic, Z.
Abstract : ( BMJ . 2022;376:e064547. doi: https://doi.org/10.1136/bmj-2021-064547 ) Two-thirds of preterm births (<37 wk gestation) occur spontaneously, while one-third are intentionally induced. Patients at risk of spontaneous preterm birth may or may not exhibit symptoms. Among high-risk patients without symptoms, cervical length <25 mm and history of spontaneous preterm birth are the 2 strongest predictors of a subsequent spontaneous preterm birth. In the United Kingdom, vaginal progesterone or cervical cerclage are the recommended interventions for preventing spontaneous preterm birth in patients with those 2 predictors, though only 16% of preterm birth clinics in the UK routinely administer vaginal progesterone in this setting. This study used network meta-analysis estimates and compares the effectiveness of vaginal progesterone and cervical cerclage in preventing spontaneous preterm birth in at-risk patients.